Hippocampal sclerosis, hippocampal neuron loss patterns and TDP‐43 in the aged population. (25th September 2017) - Hokkanen, Suvi R. K.; Hunter, Sally; Polvikoski, Tuomo M.; Keage, Hannah A. D.; Minett, Thais; Matthews, Fiona E.; Brayne, Carol; ,
Abstract: Hippocampal neuron loss is a common neuropathological feature in old age with various underlying etiologies. Hippocampal sclerosis of aging (HS‐Aging) is neuropathologically characterized by severe CA1 neuronal loss and frequent presence of transactive response DNA‐binding protein of 43 kDa (TDP‐43) aggregations. Its etiology is unclear and currently no standardized approaches to measure HS‐Aging exist. We developed a semi‐quantitative protocol, which captures various hippocampal neuron loss patterns, and compared their occurrence in the context of HS‐Aging, TDP‐43, vascular and tau pathology in 672 brains (TDP‐43 staining n = 642/672, 96%) donated for the population‐based Cambridge City over‐75s Cohort and the Cognitive Function and Ageing Study. HS‐Aging was first evaluated independently from the protocol using the most common criteria defined in literature, and then described in detail through examination of neuron loss patterns and associated pathologies. 34 (5%) cases were identified, with a maximum of five pyramidal neurons in each of over half CA1 fields‐of‐view (x200 magnification), no vascular damage, no neuron loss in CA2‐CA4, but consistent TDP‐43 neuronal solid inclusions and neurites. We also report focal CA1 neuron loss with vascular pathology to affect predominantly CA1 bordering CA2 (Fisher's exact, P = 0.009), whereas neuron loss in the subicular end of CA1 was associated with TDP‐43 inclusions (Fisher's exact, P < 0.001) and high Braak stage (Fisher's exact, P = 0.001). Hippocampal neuron loss in CA4‐CA2 was not associated with TDP‐43. We conclude that hippocampal neuron loss patterns are associated with different etiologies within CA1, and propose that these patterns can be used to form objective criteria for HS‐Aging diagnosis. Finally, based on our results we hypothesize that neuron loss leading to HS‐Aging starts from the subicular end of CA1 when it is associated with TDP‐43 pathology, and that this neurodegenerative process is likely to be significantly more common than "end‐stage" HS‐Aging only.